2016
DOI: 10.1094/phyto-01-16-0019-r
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol of Potato Common Scab is Associated with High Pseudomonas fluorescens LBUM223 Populations and Phenazine-1-Carboxylic Acid Biosynthetic Transcript Accumulation in the Potato Geocaulosphere

Abstract: Pseudomonads are often used as biocontrol agents because they display a broad range of mechanisms to control diseases. Common scab of potato, caused by Streptomyces scabies, was previously reported to be controlled by Pseudomonas fluorescens LBUM223 through phenazine-1-carboxylic acid (PCA) production. In this study, we aimed at characterizing the population dynamics of LBUM223 and the expression of phzC, a key gene involved in the biosynthesis of PCA, in the rhizosphere and geocaulosphere of potato plants gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…Biofilm formation was assessed in the three P. brassicacearum strains according to the methods described by Arseneault et al (49). Briefly, P. brassicacearum strains (wild-type LBUM300, LBUM300ΔhcnC, and LBUM300ΔphlD) were grown at 25°C for 48 h in TSB.…”
Section: Methodsmentioning
confidence: 99%
“…Biofilm formation was assessed in the three P. brassicacearum strains according to the methods described by Arseneault et al (49). Briefly, P. brassicacearum strains (wild-type LBUM300, LBUM300ΔhcnC, and LBUM300ΔphlD) were grown at 25°C for 48 h in TSB.…”
Section: Methodsmentioning
confidence: 99%
“…Biofilm formation of the bacteria was assessed in vitro after 48 h of growth following the methods described by Arseneault et al (2016). Briefly, the optical density of bacterial cells was determined after staining cells with crystal violet and subsequent destaining with 95% ethanol following growth in M9 minimal salts medium.…”
Section: Biofilm Assaymentioning
confidence: 99%
“…(Mavrodi et al, 2012a ). Phenazines produced by 2-79 and closely related species of Phz + pseudomonads exhibit broad-spectrum antibiotic activity and contribute to the capacity of these organisms to suppress several important plant pathogens (Thomashow and Weller, 1988 ; Chin-a-Woeng et al, 1998 ; Arseneault et al, 2016 ; Jaaffar et al, 2017 ). Our surveys of commercial wheat fields from throughout the Columbia Plateau revealed that the frequency of root systems colonized by Phz + bacteria is inversely correlated with annual precipitation and irrigation (Mavrodi et al, 2012a , b ).…”
Section: Introductionmentioning
confidence: 99%